2018
DOI: 10.5296/bms.v9i2.14033
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Person-Organization Value Fit in Employees’ Experience of Meaningful Work, Use of Strengths and Work Engagement

Abstract: Research in the field of management, in particular human resource management (HRM), increasingly highlights the importance of person-organization value fit. Adding to this growing body of research, this study examines the complex relation between person-organization value fit, employees’ perceptions of work, employees’ behavior at work and their well-being. More precisely, we hypothesize that person-organization value fit has a positive relationship with employees’ work engagement (well-being) via both the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
4
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 45 publications
7
4
1
Order By: Relevance
“…For this reason, a paradigm shift (including two new, “semantic dimensions,” with spiritual and work cultural [sub-]dimensions) toward the “bio-psycho-socio-spirito-cultural model” seems necessary. Moreover, our results are consistent with and extend the findings of the few previous studies regarding meaningfulness of work (Fragoso et al, 2016 ; Van Wingerden and van der Stoep, 2017 ; Van Wingerden et al, 2018a , b ), and sense of homeliness (Cicognani et al, 2009 ), in which similar moderate to high correlations were demonstrated. With respect to the studies on meaningfulness of work and burnout and meaningfulness of work and work engagement (Fragoso et al, 2016 ; Van Wingerden and van der Stoep, 2017 ; Van Wingerden et al, 2018a , b ), we obtained more differentiated evidence regarding these relationships.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…For this reason, a paradigm shift (including two new, “semantic dimensions,” with spiritual and work cultural [sub-]dimensions) toward the “bio-psycho-socio-spirito-cultural model” seems necessary. Moreover, our results are consistent with and extend the findings of the few previous studies regarding meaningfulness of work (Fragoso et al, 2016 ; Van Wingerden and van der Stoep, 2017 ; Van Wingerden et al, 2018a , b ), and sense of homeliness (Cicognani et al, 2009 ), in which similar moderate to high correlations were demonstrated. With respect to the studies on meaningfulness of work and burnout and meaningfulness of work and work engagement (Fragoso et al, 2016 ; Van Wingerden and van der Stoep, 2017 ; Van Wingerden et al, 2018a , b ), we obtained more differentiated evidence regarding these relationships.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, our results are consistent with and extend the findings of the few previous studies regarding meaningfulness of work (Fragoso et al, 2016 ; Van Wingerden and van der Stoep, 2017 ; Van Wingerden et al, 2018a , b ), and sense of homeliness (Cicognani et al, 2009 ), in which similar moderate to high correlations were demonstrated. With respect to the studies on meaningfulness of work and burnout and meaningfulness of work and work engagement (Fragoso et al, 2016 ; Van Wingerden and van der Stoep, 2017 ; Van Wingerden et al, 2018a , b ), we obtained more differentiated evidence regarding these relationships. In addition to total burnout, EE, and CY, we also considered rPE and found significant correlations between all variables.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations